Literature review on the various chemical composition of autocatalytic nickel plating - Zainuddin, Nur Asykin (2017)
Nowadays there are many techniques in preventing corrosion, one of it is electroless nickel plating, this techniques possess several characteristics not shared by other techniques causing it to raise its popularity. Innovative and less expensive substrate materials have found applications when used in conjunction with electroless nickel coatings and the method had improved the reliability of the performance of construction materials. In search for solution to reduce the cost of storage, manufacture and transportation of chemical products has resulted in increased demand for electroless nickel plating. Autocatalytic nickel plating is a chemical technique used to deposit a layer of nickel on an object or workpiece without the use of electric current or an external electrodes. It involves the presence of a chemical reducing agent. This reducing agent will reduce the nickel ions, Ni²+, to nickel metal, Ni. The recorded components of a nickel plating solution are a source of nickel ions, reducing agent, suitable complexing agent, accelerators, stabilizers or inhibitor. The other parameter of the bath such as pressure, temperature and plating rate are also considered. This study will also superficially include about the uses of electroless nickel plating in industries, the procedures of electroless nickel plating from the pre-treatment until the ultimate finishing process and the different of catalytic plating with autocatalytic nickel plating. This study is done by collecting data for these components in the bath solution from literatures available such as books, journals, reports, websites, patents and manufacturing companies.